INVENTARISASI JAMUR MAKROSKOPIS DI HUTAN BUKIT DANAU DESA PENIRAMAN KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Sabrawi, Salmiah; Turnip, Masnur; Ifadatin, Siti (Jurnal Protobiont, 2020)
Macroscopic mushrooms are one of the important biodiversity in the ecosystem of forests and human life. Research related to macroscopic mushrooms in West Kalimantan has already been done, but have never done in some areas, which is in the forest of Bukit Danau Peniraman Village of Mempawah regency. This research aims to determine the types of macroscopic mushrooms that exist in the forest of Bukit Danau Peniraman Village of Sungai Pinyuh district, Mempawah regency. Sampling of fungi using exploration methods by exploring the forest according to the transect pathway. The results showed that there were 20 types of macroscopic mushrooms consisting of 5 orders, 13 families, and 17 generas. Fungi that most commonly found came from an order of Polyporales and the fewest orders are the order ofDacrymycetales, the order of Hymenochaetales, and the order of Xylariales. Macroscopic mushrooms found in the forest of Bukit Danau Peniraman Village of Sungai Pinyuh district, Mempawah regency, fungi most commonly grew at substrate of dead tree.